Accelerating Economic Development and Improving the Current Account Balance: What Roles can Industrial Policy Play in The Gambia? - Jallow, Malick M (European Scientific Journal, ESJ, 2018)
The Gambia has been running continuous current account deficits since the 1970s owing to large merchandise importation. The GMD (Gambian money dalasi) is on a continuous gradual nose-dive. By employing a vector autoregressive model (VAR) for export determination, and a general to specific linear regression for import determination, for the period 1980-2017 and 1966-2017 respectively, this paper investigates whether the currency depreciation is causing imports (merchandise) to decline and/or causing exports to increase. Furthermore, this article addresses the need and roles industrial policy and industrialization can play in accelerating economic development in The Gambia. The empirical evidence found dictates that a depreciation of the GMDis neither causing a decline in imports nor an increase in exports. Underpinned by the research outcome, we suggest that policymakers implement EOI (export-oriented industrialization) and ISI (imports substitution industrialization) industrialization strategy mix to expedite economic development, correct the long-standing current account deficits and curb the currency depreciation. Given the global economic environment, and the smallness of the Gambia’s economy relative to its trading partners, we put forward that the implementation of these strategies is in a framework of engaging the public, private and foreign sectors.